2012
DOI: 10.1590/s0034-737x2012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância à seca de genótipos de trigo utilizando agentes indutores de estresse no processo de seleção

Abstract: Drought tolerance of wheat genotypes using stress-inducing agents during selectionThe aim of this study was to select wheat genotypes tolerant to drought by inducing water deficit using different osmotic agents. Seeds and immature embryos of eight wheat genotypes were subjected to different osmotic gradients and evaluated for shoot length, main root and total biomass production. Seeds were subjected to the osmotic agents polyethyleneglycol-6000 and mannitol in seven osmotic gradients and evaluated after 10 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
6
0
6
Order By: Relevance
“…The effect of different water potentials on the physiology and morphology of various species, such as common bean (CUSTÓDIO; SALOMÃO; MACHADO NETO, 2009;YAMAMOTO et al, 2014), wheat (GIROTTO et al, 2012), and sunflower (HÄTER et al, 2014) has been intensively studied in order to elucidate the effects of water deficiency, as well as the mechanisms of response to the water stress. The authors, evaluating the effect of different water potentials during germination and initial growth stages, observed a decrease in growth with an increase in water restriction, a behavior explained by the reduction in cell elongation, with a consequent increase in the synthesis of the secondary wall under water stress (CARVALHO; NAKAGAWA, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of different water potentials on the physiology and morphology of various species, such as common bean (CUSTÓDIO; SALOMÃO; MACHADO NETO, 2009;YAMAMOTO et al, 2014), wheat (GIROTTO et al, 2012), and sunflower (HÄTER et al, 2014) has been intensively studied in order to elucidate the effects of water deficiency, as well as the mechanisms of response to the water stress. The authors, evaluating the effect of different water potentials during germination and initial growth stages, observed a decrease in growth with an increase in water restriction, a behavior explained by the reduction in cell elongation, with a consequent increase in the synthesis of the secondary wall under water stress (CARVALHO; NAKAGAWA, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Girotto et al (2012), evaluating the behavior of wheat genotypes at different water potentials induced by PEG 6000 and mannitol, observed that at a potential of −0.4 MPa, or at more negative potentials, the growth of the seedlings decreased by at least 50%, but varied among the genotypes.…”
Section: Figure 2 Seedling Height -Sh (A C and E) Total Dry Phytommentioning
confidence: 99%
“…hídrico proporciona reduções significativas no rendimento das lavouras, restringindo as latitudes e os solos onde espécies comercialmente importantes podem ser cultivadas (Girotto et al 2012). Na germinação das sementes, a ocorrência do estresse hídrico atua diminuindo a velocidade e a porcentagem de germinação.…”
Section: Key-wordsunclassified
“…Estes resultados podem ser atribuídos ao déficit hídrico das plantas, resultante da evaporação da água do meio de cultura no recipiente com maior aeração (algodão) em relação aos demais fechamentos testados. O défict hídrico é um importante fator limitante do crescimento e desenvolvimento da planta, levando a modificações morfológicas, bioquímicas e fisiológicas, e consequentemente afetando a sua sobrevivência (GIROTTO et al, 2012;HOMAYOUN;DALIRI;MEHRAB, 2011).…”
Section: Resultsunclassified